Exploring communicative language teaching to enhance grammatical knowledge among secondary school students in Bangladesh - Ummeh Rokaiya; Saharuddin, Norzihani (Macrothink Institute, 2022)
Communicative Language Teaching (CLT) involves students in real-life interaction in order to improve their communicative competence. There are a lot of controversy about whether grammatical knowledge can be gained by CLT in the English learning process. This qualitative case study goals to attain the perspective and attitudes of students and explore the implementation of CLT in Bangladeshi Secondary School. Moreover, researcher aims to reach the gap which is emerged by the controversy. It attempted to find out the contribution of CLT in improving grammar knowledge among Secondary School Students in Bangladesh. Researcher investigated two research questions and examined two research objectives. Data was collected through semi-structured interview and an essay writing task from Dr. Khastagir Government Girls’ High School, Bangladesh. The finding of study indicates efficient and feasible CLT activities are explored in the textbook which engaged students in collaborative learning and meaningful interaction. Students have a certain perspective and an assured outlook towards CLT based classroom and they have a knowledgeable linguistic competence in writing. Besides, in acquiring communicative skills, fluency and accuracy were not attained equally among the students. Besides, students were aware of both in grammar knowledge and meaningful interaction but faced few obstacle in speaking. Accuracy activities of CLT facilitate to enhance grammar knowledge but a little lack was explored from the findings. To say, this study provides an insight on positive perspective of students towards communicative classroom settings.